ANALYZING TIME EFFECT IN THE PUSH AND PULL FACTORS AFFECTING FOREIGN PORTFOLIO INVESTMENT IN INDONESIA STOCK MARKET (CASE STUDY OF FOREIGN BUYING DURING THE PERIOD 2003-2018) - Mustafa, Matrodji; Hamid, Agustini (Dinasti International Journal of Management Science, 2021)
This study examined the influence of pull and push factors on foreign portfolio investment in Indonesia Stock Market. Two measures of foreign portfolio investment are foreign investor total buying and foreign investor net buying. The pull factors are represented by Return on Jakarta Composite Index, Jakarta Stock Marker liquidity, IDR Exchange Rate, and Infation Rate. The push factors included are return on Dow Jones Industrial Average, Yield on US Treasury Bill, and return on Gold. This study takes Foreign Investor Total Buying and Foreign Investor Net Buying as dependent variables. To accomodate time or year effect, a panel data regression is employed as analytical tool. Processing monthly data from January 2003 to December 2018, and using Foreign Investor Total Buying as dependent variable, this study finds that exchange rate and stock market liquidity affect the foreign investor total buying significantly. The negative coefficients of exchange rate and the positive coefficient of stock market liquidity support the hypotheses. The regression on Net Buying shows that exchange rate, stock market return, and stock market liquidity affect foreign investor net buying significantly. The negative coefficient of exchange rate and positive coefficient of stock market return support the hypotheses while the negative coefficient of stock market liquidity does not. The individual year fixed effect and individual year random are present in the first and second regressions repectively. In both regressions, no variables in push factors affect foreign portfolio investment significantly. hence, the foreign portfolio investment in Indonesia is affected only by pull factors